2022
DOI: 10.12911/22998993/146679
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Composition of Organic Matter and Properties of Humic Acids in the Soils of Drained Bogs of the Siedlce Heights in Eastern Poland

Abstract: The studied bogs of the Siedlce Heights in eastern Poland are currently undergoing decession. In the course of pedological studies, a significant modification of the structure of soil profiles caused by the murshing process was found. The total contents of carbon and nitrogen values (TC/TN = 11.1-17.3) obtained in the study, as well as slight acidification (pH KCl 5.42-6.15) indicate the eutrophy of the studied soil environment, high biological activity and a significant degree of organic matter processing as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 8 publications
5
14
1
Order By: Relevance
“…Ukalska-Jaruga et al (2019) observed almost similar trends (i.e., AF>AH rates) on arable and grassland soils with lower HS contents for arable sites. With higher humic fractions than those of our study, Becher et al (2022) on the contrary found HA fractions more abundant than FA in all peat profiles. Inappropriate agricultural practices accelerate OM mineralization and change from FA to HA abundance or inversely (Ukalska-Jaruga et al, 2019).…”
Section: Fulvic Acid Humic Acid and Humin Fractionscontrasting
confidence: 98%
“…Ukalska-Jaruga et al (2019) observed almost similar trends (i.e., AF>AH rates) on arable and grassland soils with lower HS contents for arable sites. With higher humic fractions than those of our study, Becher et al (2022) on the contrary found HA fractions more abundant than FA in all peat profiles. Inappropriate agricultural practices accelerate OM mineralization and change from FA to HA abundance or inversely (Ukalska-Jaruga et al, 2019).…”
Section: Fulvic Acid Humic Acid and Humin Fractionscontrasting
confidence: 98%
“…Compared against the results of Jonczak (2013), Drąg et al (2007) and Kobierski et al (2018), it was found that the tested HA molecules had lower A 4/6 absorbance coefficients and ΔlogK absorbance coefficients. It is worth emphasizing that the tested HAs had slightly higher values of the A 4/6 and ΔlogK absorbance coefficients than do HAs in peat soils (Becher et al, 2022). Filcheva et al (2018) hold that there is a direct relationship between the groups with prevailing HAs or FAs in the humic products and the A 4/6 ratio.…”
Section: Properties Of Humic Acidsmentioning
confidence: 89%
“…The results of the meadow soil tests presented by Drąg et al (2007) corresponded with the examined HA molecules, exhibiting similar values of H/C, O/H and the ω parameter. However, compared to the properties of HAs in peat soils (Becher et al, 2022) and Chernozems (Łabaz, 2010), the tested HAs had a lower degree of maturity, as evidenced by higher H/C ratios and lower ω parameter values.…”
Section: Properties Of Humic Acidsmentioning
confidence: 90%
“…Strong binding of mercury in soils is due to its high chemical affinity for organic matter [4,6,18,[49][50][51]. Peatland drainage (very frequent in case of utilisation of organic soils) stimulates aerobic organic matter decomposition, production of dissolved organic matter (DOM) and humic substances (HS) [52][53][54][55]. Dissolved organic matter affects mercury speciation, mobility and toxicity in the environment [8,9,19,50,[56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Peatland drainage for farming purposes is a major cause of fen peatland degradation in the temperate climate [69]. Peat degradation is followed by the formation of a murshic horizons which has an aggregate structure and a greater quantity of humic substances [52,54,68,70]. The process of peatland drainage is progressing due to climatic change which contributes to a negative water balance that is unfavourable for peatland development [71,72].…”
Section: Introductionmentioning
confidence: 99%